Literature Review of Value of Faecal Sludge - Mallory, Adrian (Cranfield University, 2020)
This spreadsheet presents data from a literature review of sanitation in Africa and Asia to assess the value of resource recovery from faecal sludge management. It presents the reference, location, theory score, value of product converted to dollars using Market Exchange and Parity Purchasing Parity rates.
Keywords: faecal sludge management'; 'sanitation'; 'circular economy'; 'sub-saharan africa'; 'resource recovery'; 'Water Resources Engineering'; 'Wastewater Treatment Processes'